Functional Analysis of KIT Gene Structural Mutations Causing the Porcine Dominant White Phenotype Using Genome Edited Mouse Models - Sun, Guanjie; Liang, Xinyu; Qin, Ke; Qin, Yufeng; Shi, Xuan; Cong, Peiqing; Mo, Delin; Liu, Xiaohong; Chen, Yaosheng; He, Zuyong (Frontiers in Genetics, 2020)
The dominant white phenotype in pigs is thought to be mainly due to a structural mutation in the KIT gene, a splice mutation (G > A) at the first base in intron 17 which leads to the deletion of exon 17 in the mature KIT mRNA. However, this theory has not yet been validated by functional studies. Here, we created two mouse models, KIT D17/+ to mimic the splice mutation, and KIT Dup/+ to partially mimic the duplication mutation of KIT gene in dominant white pigs using CRISPR/Cas9 technology. We found that the splice mutation homozygote is lethal and the heterozygous mice have a piebald coat. Increased expression of KIT in KIT Dup/+mice did not confer the patched phenotype and had no obvious impact on coat color. Interestingly, the combination of these two mutations reduced the phosphorylation of PI3K and MAPK pathway associated proteins, which may be related to the impaired migration of melanoblasts observed during embryonic development that eventually leads to the dominant white phenotype.